Sesamol Loaded Albumin Nanoparticles: A Boosted Protective Property in Animal Models of Oxidative Stress - Sara Zaher; Mahmoud E. Soliman; Mahmoud Elsabahy; Rania M. Hathout (MDPI AG, 2022)
The current study evaluated the ability of sesamol-loaded albumin nanoparticles to impart protection against oxidative stress induced by anthracyclines in comparison to the free drug. Albumin nanoparticles were prepared via the desolvation technique and then freeze-dried with the cryoprotectant, trehalose. Albumin concentration, pH, and type of desolvating agent were assessed as determining factors for successful albumin nanoparticle fabrication. The optimal nanoparticles were spherical in shape, and they had an average particle diameter of 127.24 ± 2.12 nm with a sesamol payload of 96.89 ± 2.4 μg/mg. The drug cellular protection was tested on rat hepatocytes pretreated with 1 µM doxorubicin, which showed a 1.2-fold higher protective activity than the free sesamol. In a pharmacokinetic study, the loading of a drug onto nanoparticles resulted in a longer half-life and mean residence time, as compared to the free drug. Furthermore, in vivo efficacy and biochemical assessment of lipid peroxidation, cardiac biomarkers, and liver enzymes were significantly ameliorated after administration of the sesamol-loaded albumin nanoparticles. The biochemical assessments were also corroborated with the histopathological examination data. Sesamol-loaded albumin nanoparticles, prepared under controlled conditions, may provide an enhanced protective effect against off-target doxorubicin toxicity.